Islamic Fintech and Digital Islamic Economic Development: Opportunities and Challenges in Supporting Sustainable Community Welfare - Nurul Istifadhoh (STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
Fintech is a financial services method that is gaining popularity in today's digital era. Digital payments are one of the fastest-growing sectors in the fintech industry in Indonesia. Sustainable development is used as a human effort to improve the quality of life while still striving not to overwhelm the ecosystem that supports life, and is always considered a crucial issue in society. The aim of this research is to determine whether fintech can become a solution for sustainable development in Indonesia. The research method used is qualitative descriptive with a literature study approach. The results show that fintech implementation is considered one solution for improving sustainable development goals to optimize the realization of public welfare. On the other hand, fintech implementation still requires various preparations that must be met first by the government, including customer data security, digital literacy, financial literacy, and infrastructure for every fintech activity